Jogos culturais na educação física escolar (um relato de experiência a partir do estágio supervisionado) - Saldanha, Maria Eduarda Holanda da Silva (BRASIL, 2023)
This Course Conclusion Paper aimed to highlight the contribution of Cultural Games in School Physical Education, b. One of the contents that can help students to elucidate their realities is the Cultural Game. To do so, the methodology used was exploratory research, with bibliographic research including scientific articles, monographs, books, and others. Given the study, the reading and interpretation of the selected sources, it consists of an experience report that integrates the theoretical construction and the experiences lived during the supervised internship, concepts and importance of how cultural games help the development of students, emphasizing the relevance of rescuing these games in the context of Physical Education at school. At the end of the research, it was possible to understand that it is possible to treat several types of knowledge and cultural concepts, when taking games to the routines of elementary I physical education, having a result of stimulating motor development and skills. The supervised internship is fundamental to put into practice all the theoretical foundation acquired during the academic formation.